(untitled) (TAMADDUN NURI JURNALI, 2024)
This article dives into the world of concepts, explaining what they are and the different types that exist. It explores how concepts help us organize our thoughts and communicate effectively. Additionally, it delves into the concept of age, breaking it down into its various dimensions such as chronological, biological, psychological, and social. By exploring these topics in simple language, the article offers valuable insights into how we perceive and navigate the world around us. It’s an informative read for those interested in understanding the fundamental aspects of human cognition and development.